Comparative Genomics Provides Insight into the Diversity of the Attaching and Effacing Escherichia coli Virulence Plasmids - Hazen, Tracy H. (Infect Immun, 2015)
Attaching and effacing Escherichia coli (AEEC) strains are a genomically diverse group of diarrheagenic E. coli strains that are characterized by the presence of the locus of enterocyte effacement (LEE) genomic island, which encodes a type III secretion system that is essential to virulence. AEEC strains can be further classified as either enterohemorrhagic E. coli (EHEC), typical enteropathogenic E. coli (EPEC), or atypical EPEC, depending on the presence or absence of the Shiga toxin genes or bundle-forming pilus (BFP) genes. Recent AEEC genomic studies have focused on the diversity of the core genome, and less is known regarding the genetic diversity and relatedness of AEEC plasmids. Comparative genomic analyses in this study demonstrated genetic similarity among AEEC plasmid genes involved in plasmid replication conjugative transfer and maintenance, while the remainder of the plasmids had sequence variability. Investigation of the EPEC adherence factor (EAF) plasmids, which carry the BFP genes, demonstrated significant plasmid diversity even among isolates within the same phylogenomic lineage, suggesting that these EAF-like plasmids have undergone genetic modifications or have been lost and acquired multiple times. Global transcriptional analyses of the EPEC prototype isolate E2348/69 and two EAF plasmid mutants of this isolate demonstrated that the plasmid genes influence the expression of a number of chromosomal genes in addition to the LEE. This suggests that the genetic diversity of the EAF plasmids could contribute to differences in the global virulence regulons of EPEC isolates.